x-1=-1 система
y^2-7x=7
x=0 система
y^2-7*0=7
y=-
y=
(x1,y1)=(0,-)
(x2,y2)=(0,)
0-1=-1 система
(-)^2-7*0=7
^2-7*0=7
-1=-1 система
7=7
Объяснение
ответ: (0;√7); (0;-√7)
Объяснение:
из первого уравнения. х=-1+1=0
подставим во второе. получим у²-7*0=7, откуда у=±√7
имеем два решения (0;√7); (0;-√7)
x-1=-1 система
y^2-7x=7
x=0 система
y^2-7x=7
y^2-7*0=7
y=-![\sqrt{7}](/tpl/images/4806/6463/69133.png)
y=![\sqrt{7}](/tpl/images/4806/6463/69133.png)
(x1,y1)=(0,-
)
(x2,y2)=(0,
)
0-1=-1 система
(-
)^2-7*0=7
0-1=-1 система
-1=-1 система
7=7
-1=-1 система
7=7
(x1,y1)=(0,-
)
(x2,y2)=(0,
)
Объяснение
ответ: (0;√7); (0;-√7)
Объяснение:
из первого уравнения. х=-1+1=0
подставим во второе. получим у²-7*0=7, откуда у=±√7
имеем два решения (0;√7); (0;-√7)